As condições de trabalho de professores temporários: uma análise a partir da política de contratação do município de Santana-AP (2011-2023) - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
This work is linked to the Educational Policies line of the Graduate Program in Education at the Federal University of Amapá (PPGED/UNIFAP). Its research topic is temporarily hired teachers, focusing on the working conditions resulting from the hiring policy in the municipality of Santana. Temporary hiring is a type of employment relationship that occurs outside the framework of admission through public examinations. Within the public service, this hiring must be exceptional and provisional, specifically permitted in cases of replacement of civil servants due to medical leave, vacancies, or absences. According to the 1988 Federal Constitution, regular admission to the public service occurs primarily through public examinations. However, with the advent of neoliberal rationality in the management of public and social policies, especially educational ones, there has been an exponential increase in this type of temporary hiring in basic and higher education. Studies indicate that this policy is expanding through reduced investment in education and the precariousness and flexibilization of labor relations, stemming from the crisis of capitalism's mode of accumulation. Given this scenario, this study aimed to analyze the working conditions of temporary teachers, specifically regarding their recruitment, compensation, rights, and guarantees. Methodologically, the investigation was conducted through bibliographic and documentary research. The documents analyzed consist of local laws on temporary hiring, the Position, Career, and Compensation Plan (Law No. 849/2010), the Municipal Education Plan, the Organic Law of the municipality of Santana, and the Conduct Adjustment Agreement (TAC) signed between the Public Prosecutor's Office and the Santana City Hall. The examination of documents obtained from the Santana City Hall, the Municipal Department of Education (SEME), and the Santana Public Prosecutor's Office was conducted based on Bardin's Content Analysis.
Keywords: Política educacional; Trabalho docente; Condições de trabalho; CNPQ::CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL::POLITICA EDUCACIONAL; ODS 16 – Paz, justiça e instituições eficazes; ODS 8 – Trabalho decente e crescimento econômico; ODS 4 – Educação de qualidade